How People Respond to Violence Everyday Peace and the Maoist Conflict in India - Carrer, Monica (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the powerful role of ordinary people's agency in times of violent conflict. Drawing on extensive fieldwork and a Critical Discourse Analysis, the author draws out the motivations, drivers and strategies at individual and community levels. With a focus on people's own voices, this research highlights rich findings showing a wide range of experiences and actions that people engaged in during the violent conflict, and dimensions that are often missed in dominant explanations of violent conflict. Therefore, while looking at peace and conflict from an everyday perspective, the question of power and the meaning of peace knowledge become central. This monograph addresses the power of people's agency not only in shaping the politics and dynamics of violence, but also in redefining what 'peace' and 'change' ought to look like. Essential reading for researchers and students of Peace and Conflict Studies, and also International Relations, Security Studies, Resistance Studies, Anthropology, Politics, International Development. Monica Carrer, co-founder of the Everyday Peace Initiative and the creator of the Everyday Peace Community, a digital platform and app dedicated to peace and social change that crowdsources knowledge for peace and social change action, connecting researchers with activists, practitioners and communities. She is co-author of the Everyday Peace Toolkit and recipient of the Sonja Davies Peace Award.
1. A Puzzle From the Field -- 2. Local People in the Civil Wars Literature -- 3. Maoism in India -- 4. An Everyday Approach to Conflict and Peace -- 5. The Lalgarh Movement in Junglemahal: Comparing the Narratives -- 6. Experiencing Conflict -- 7. Responding to Conflict -- 8. Perspectives on Peace, Change and Development -- 9. Conclusion: The Extraordinary of the Ordinary in Times of Violence.
Keywords: Peace; Terrorism; Political violence; International relations; Anthropology; Peace and Conflict Studies; Terrorism and Political Violence; International Relations; Anthropology